Effects of doping on magnetic and transport properties of La₀.₈₅₋ₓSmₓAg₀.₁₅MnO₃, La₀.₈₅₋ₓMₓAg₀.₂MnO₃ (M=Sm³⁺, Dy³⁺), (1₋ₓ)La₀.₈Ag₀.₂MnO₃/xBiFeO₃ And Pr₀.₆Ca₀.₄₋ₓBaₓMnO₃ Manganites / Norazila Ibrahim - Ibrahim, Norazila (Institute of Graduate Studies, UiTM, 2015)
In this study, four manganites series with starting compositions La₀.₈₅₋ₓSmₓAg₀.₁₅MnO₃(x=0-0.2), La₀.₈₋ₓMₓAg₀.₂MnO₃ (M= Dy³⁺, Sm³⁺x=0-0.15), (1-y) La₀.₈Ag₀.₂MnO₃/yBiFeO₃ (y=0wt%-3.5wt%) and Pr₀.₆Ca₀.₄₋ₓBaxMnO₃ (x=0-0.3) were prepared by solid-state reaction method in order to elucidate their physical properties. For La₀.₈₅₋ₓSmₓAg₀.₁₅MnO₃ (x=0-0.2) and La₀.₈₅₋ₓMₓAg₀.₂MnO₃ (M=Sm³⁺, Dy³⁺, x=0-0.15) series, the resistivity and magnetic measurements showed all samples exhibit transition from insulating to metallic behavior accompanying a paramagnetic to ferromagnetic transition as the temperatures was decreased. For x=0, two metal-insulator, MI transition peaks were observed at TP1 and TP2 in the resistivity curves. Both peaks and Curie temperature, Tc shifted to lower temperatures with increasing Dy³⁺and Sm³⁺, indicating that the substitution weakened the double exchange process and enhanced the Jahn-Teller effect. The magnetoresistance peak was observed around TP1 for all samples. The observed double peak behavior in the ρ(T) curve is suggested to be due magnetic inhomogeneity of the samples. Our result also showed that the inhomogeneity was strongly influenced by the lattice effect...